Mammals from the Salicas formation (Late Miocene), La Rioja Province, northwestern Argentina : Paleobiogeography, age, and paleoenvironment - Brandoni, Diego (2012)
Fil: Brandoni, Diego. Laboratorio de Paleontología de Vertebrados. Centro de Investigaciones Científicas y Transferencia de Tecnología a la Producción; Diamante; Argentina